2011
DOI: 10.1097/won.0b013e31820af380
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Multi-intervention Incontinence Care Program on Clinical, Economic, and Environmental Outcomes

Abstract: Results of this study suggest that a multi-intervention program, including introduction of new absorbent products, a structured skin hygiene program, and advice from continence nurses, reduce the relative risk of IAD, absorbent product use, and generation of waste materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 18 publications
1
26
0
5
Order By: Relevance
“…In the guide, each NANDA‐I diagnosis was defined, and its etiology was supported with literature (Herdman & Kamitsuru, ). In this study, similar to the literature, elderly women showed more urge incontinence and stress‐type incontinence and less reflex type incontinence nursing diagnosis (Thüroff et al., ; Palese & Carniel, ). Nurses with different levels of education and experience who provide care for elderly women with UI evaluate the elderly with UI in terms of incontinence.…”
Section: Nanda‐isupporting
confidence: 89%
“…In the guide, each NANDA‐I diagnosis was defined, and its etiology was supported with literature (Herdman & Kamitsuru, ). In this study, similar to the literature, elderly women showed more urge incontinence and stress‐type incontinence and less reflex type incontinence nursing diagnosis (Thüroff et al., ; Palese & Carniel, ). Nurses with different levels of education and experience who provide care for elderly women with UI evaluate the elderly with UI in terms of incontinence.…”
Section: Nanda‐isupporting
confidence: 89%
“…In the current study, the total daily cost of IAD management per patient was higher for the intervention group (trueX¯ = $135.68 ± 61.24) than the control group (trueX¯ = 108.77 ± 48.25), which can be linked to the relatively higher prevalence of urinary and fecal incontinence in the intervention group and the more frequent management of incontinence. In the literature, the majority of IAD management and treatment is associated with the care time (Beeckman et al., ; Bliss et al., ; Palese & Carniel, ). In our study, similarly to the literature, the cost of the nursing workforce for IAD management was relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…Protecting the tissue integrity of patients during their hospital stay is one of the most important goals of health care (Beeckman et al., ; Brem et al., ). In particular, evidence‐based (EB) nursing initiatives have been shown to increase tissue tolerance and can also be cost‐effective (Gardiner et al., ; Palese & Carniel, ). In order to maintain tissue integrity, tissue tolerance must be increased.…”
Section: Background and Significancementioning
confidence: 99%
“…(), who reported a successful experience in managing women's UI through a multidisciplinary and multi‐institutional network. Palese and Carniel () also showed that a multi‐intervention program, including structured skin hygiene care by nursing assistants, professional education, assessment, and individualized consultation by a continence nurse, was helpful in decreasing the relative risk of incontinence‐associated dermatitis in nursing home patients and reducing the daily production of waste.…”
Section: Discussionmentioning
confidence: 99%